2011
DOI: 10.1007/s10902-011-9275-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Wisdom and Happiness: An Empirical Investigation

Abstract: Possible tensions between wisdom and happiness have been extensively debated in philosophy. Some regard wisdom as the 'supreme part of happiness', whereas other think that a more accurate and wiser view on reality might reduce happiness. Analyzing a Dutch internet survey of 7037 respondents, we discovered that wisdom and happiness were modestly positively related. Wisdom, measured with the Three-Dimensional Wisdom Scale (3D-WS), explained 9.2% of the variation in hedonic happiness. The correlation with the ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 69 publications
(92 reference statements)
4
46
1
6
Order By: Relevance
“…Based on the existing American (Ardelt, 1997(Ardelt, , 2003(Ardelt, , 2009), Dutch (Bergsma & Ardelt, 2012), and Polish studies (Wilk, 2010;Sasiela, 2013;Wojciechowska, 2013;Falewicz, 2014;Niemczyk, 2014), we hypothesized a three-factor structure of wisdom as measured using 3D-WS by M. Ardelt (2003).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the existing American (Ardelt, 1997(Ardelt, , 2003(Ardelt, , 2009), Dutch (Bergsma & Ardelt, 2012), and Polish studies (Wilk, 2010;Sasiela, 2013;Wojciechowska, 2013;Falewicz, 2014;Niemczyk, 2014), we hypothesized a three-factor structure of wisdom as measured using 3D-WS by M. Ardelt (2003).…”
Section: Methodsmentioning
confidence: 99%
“…Validity analyses demonstrated that the measure is positively correlated with self-control (.63), psychological well-being (.45), sense of purpose in life (.61), and subjective sense of health (0,30), as well as significantly negatively correlated with depressive symptoms (-.59) and death anxiety (-.56) (Ardelt, 2003). The Three--Dimensional Wisdom Scale is a valuable measure of wisdom and is used in numerous empirical studies, especially with subjects in their late adulthood (Ardelt, 2004(Ardelt, , 2005(Ardelt, , 2008(Ardelt, , 2009(Ardelt, , 2010(Ardelt, , 2011Bergsma & Ardelt, 2012;Taylor, Bates, & Webster 2011;Asadi, Amiri, Molavi, & Noaparast, 2012).…”
Section: The Original Version Of the Three-dimensional Wisdom Scale (mentioning
confidence: 99%
See 1 more Smart Citation
“…Wciąż jednak obserwuje się brak powszechnej zgody odnośnie do rozumienia samego pojęcia "mądrość" (Dittmann-Kohli i Kramer, 2000;Bergsma i Ardelt, 2012). Psychologiczne badania nad mądrością, pomimo iż mają stosunkowo krótką historię (Kunzmann i Baltes, 2005), zaowocowały wieloma propozycjami ujęcia tego konstruktu w koncepcyjne ramy (Olejnik i Niemczyński, 1993;Birren i Svensson, 2005;Osbeck i Robinson, 2005;Trowbridge, 2005;Brugman, 2006;Staudinger, 2008;Meeks i Jeste, 2009;Bangen, Meeks i Jeste, 2013).…”
Section: Wprowadzenie Teoretyczneunclassified
“…Analizy trafności dowiodły, iż narzędzie wykazuje pozytywne korelacje z samokontrolą (0,63), dobrostanem psychicznym (0,45), poczuciem celu w życiu (0,61) oraz subiektywnym poczuciem zdrowia (0,30), a także znaczące i negatywnie związki z objawami depresyjnymi (-0,59) czy lękiem przed śmiercią (-0,56) (Ardelt, 2003). Trzywymiarowa Skala Mądrości stanowi wartościowe narzędzie do pomiaru mądrości życiowej i jest wykorzystywana w licznych badaniach empirycznych, zwłaszcza w odniesieniu do osób w późnej dorosłości (Ardelt, 2004(Ardelt, , 2005(Ardelt, , 2008(Ardelt, , 2009(Ardelt, , 2010(Ardelt, , 2011Bergsma i Ardelt, 2012;Taylor, Bates i Webster 2011;Asadi, Amiri, Molavi i Noaparast, 2012).…”
Section: Oryginalna Wersja Trzywymiarowej Skali Mądrości (3d-ws)unclassified